Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea) - Colavite, Jessica [UNESP]; Santana, William; Tavares, Marcos (Magnolia Press, 2016)
Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) have been treated either as subspecies or as species in their own right, but never as each other's synonyms. Compared to S. coelatus, S. furcatus has been regarded as having smoother dorsal surface carapace, shorter rostral spines, straighter and less divergent rostrum. and smaller interorbital width. These morphological differences between the two species, however, can be attributed to changes over ontogeny and, therefore, cannot be used as distinguishing characters. Adults of S. coelatus and S. furcatus can, however, be safely separated from each other by the presence in S. coelatus of a strong crenation on the anterior margin of the male sterno-abdominal cavity, which is absent in S. furcatus. A lectotype for S. coelatus is designated. The synonymy between S. furcatus, Cancer cornudo Herbst, 1804, and Chorinus armatus Randall, 1839, is confirmed based on the holotypes of the latter two species.
Keywords: Epialtidae; Mithracidae; spider crab; Western Atlantic; subspecies; ontogeny